Religiosity and Consumer Ethical Beliefs - Rathnayake, D.T.; Jayakody, J.A.S.K; Jayawardana, A.K.L. (My University, 2017)
Business ethics have been a major concern for society for a long time. However, relatively few studies have tried to examine the ethical issues of the marketing process from a consumer’s point of view, Moreover, among the many determinants of consumer ethics, religiosity has been a little examined facet that, nevertheless, has had a strong influence on consumer ethical beliefs. Therefore, this paper attempts to examine the impact of religiosity on consumer ethical beliefs. This paper has used the “quest” dimension of religiosity, which is outlined in the extant literature, along with intrinsic and extrinsic dimensions so that the complete domain of religiosity would be captured. Based on a rigorous literature review, it was hypothesized that there is an impact of intrinsic religiosity, extrinsic religiosity and quest religiosity on consumer ethical beliefs. In addition, an interaction between intrinsic and extrinsic religiosity was hypothesized, while the final proposition argued that intrinsic religiosity is a stronger predictor of ethical beliefs than extrinsic religiosity. The study was quantitative, while the crosssectional (survey) design was chosen as the overall research design. Data was analyzed using Structural Equation Modeling (SEM) to test the hypotheses, and data analysis revealed that there is an impact of intrinsic, extrinsic and quest religiosity on consumer ethical beliefs. The findings of the study emphasize the role of ethics education, and consumer socialization in ensuring consumer ethics. Furthermore, this study urges managers to use ethical appeal in advertising and adopt relationship marketing strategies instead of using punitive actions to control the unethical behaviours of consumers. Keywords: Consumer ethical beliefs, Religiosity, Extrinsic religiosity, Intrinsic religiosity, Quest religiosity